Peningkatan Kapasitas Kader Posyandu Melalui Pelatihan Pemantauan Status Gizi Balita - Ibnu Zaki; Farida Farida; Hesti Permata Sari (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2018)
Early childhood represents the stage of golden period during children development. Nutritional status monitoring at this period is very important to prevent growth disorders. The monitoring process is conducted monthly through posyandu. Posyandu cadres are the spearhead of successful nutritional status monitoring for children under five years old, therefore increasing cadres’ capability is necessary. This activity aims to improve posyandu cadres’ capability including knowledge and skills for nutritional status monitoring of children under five years old. This activities were carried out at Posyandu Mawar VI Karangsalam Kidul, Kedungbanteng Sub-District, Banyumas District, Central Java. This series of activities are conducted for four months, from May to August, 2017. The activity method was training with simulation with seven cadres participated in this activity. The evaluation resulted in increase of knowledge and skill level of cadre in nutritional status monitoring. The increase of knowledge scoring before and after training equal to 1.88 points. The increase of skill showed by almost every measurements are conducted properly, such as weighing standing toddler, weighing baby weight less than two years old, height measurement of toddler, and plotting KMS. Whereas, cadres are still having difficulties in measuring the length of the baby. It can be concluded that there is an increase in knowledge and skills of posyandu cadres in nutritional status monitoring of children after training.